Microalloying method for inhibiting precipitation of Cr-sigma-rich phase in (CrCoNi) 94Al3Ti3 medium-entropy alloy
By introducing B element into the entropy alloy of CrCoNi94Al3Ti3, the precipitation of the Cr-sigma-rich phase is suppressed, and the problem of overlapping with the precipitation temperature range of the L12 phase is solved, improving the corrosion resistance of the material and its stability in complex environments.
Patent Information
- Application Number
- CN202411298735.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-24
AI Technical Summary
The Cr-sigma-rich phase in CrCoNi medium entropy alloy overlaps the precipitation temperature interval of the excellent L12 phase, resulting in the Sigma phase inevitably precipitation during aging strengthening, affecting the plastic toughness and corrosion resistance of the material, especially in environments such as high temperature and seawater. .
B element is introduced into the entropy alloy in CrCoNi94Al3Ti3, so that it is distributed at the phase interface of the Cr-sigma-rich phase, limiting its growth, and suppressing the precipitation of the Cr-sigma-rich phase through microalloyization treatment.
The size and quantity of Cr-sigma-rich phases are effectively controlled, the corrosion resistance of the material is improved, its instability in high temperature environments is avoided, and its application ability is enhanced in complex environments.
Smart Images

Figure CN119177389A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation and application of CrCoNi medium entropy alloy, and in particular to a method for inhibiting (CrCoNi) 94 Microalloying method for precipitation of Cr-rich sigma phase in Al3Ti3 medium entropy alloy. Background Art
[0002] In recent years, the new hot spots and new stages of physical metallurgy research have focused on alloy materials composed of multiple main alloying elements. In comparison, traditional alloys are often generated by one main metal, and the proportion of other elements is relatively low. This type of new alloy is a multi-principal alloy, also known as a high entropy alloy (HEA) or a medium entropy alloy (MEA). At present, compared with high entropy alloys, medium entropy alloys have a relatively simple system and also show many excellent high and low temperature, mechanical and corrosion resistance properties, and have good application prospects. Among them, the CrCoNi system containing a small amount of Al and Ti is the most widely studied medium entropy alloy system, because it can form an L12 phase with excellent temperature stability that is coherent with the matrix through aging heat treatment, which significantly improves its high and low temperature mechanical properties. However, the precipitation temperature range of the L12 phase as a strengthening phase overlaps with the precipitation temperature range of the harmful Cr-rich sigma phase, resulting in the inevitable precipitation of a large amount of Sigma phase while aging strengthening. This hard and brittle precipitation phase seriously affects the plastic toughness of the material and deteriorates the corrosion resistance, resulting in poor high temperature stability and poor corrosion resistance in environments such as seawater. Therefore, finding a method to inhibit the precipitation of Cr-rich sigma phase, improve grain boundary brittleness and enhance corrosion resistance is of great significance for the simultaneous improvement of strength and corrosion resistance of medium-entropy alloys based on CrCoNi with harmful grain boundary Cr-rich sigma phase precipitation. Summary of the invention
[0003] In view of this, the present invention aims to provide a method for inhibiting (CrCoNi) 94 A microalloying method for precipitation of Cr-rich sigma phase in Al3Ti3 medium entropy alloy, the present invention is to (CrCoNi) 94 The B element, which is easy to segregate to the phase interface, is introduced into the Al3Ti3 medium-entropy alloy, so that the B element is distributed at the phase interface of the Cr-rich sigma phase to limit the growth of the Cr-rich sigma phase and control the initial Cr-rich sigma phase size.
[0004] In order to achieve the above object, the present invention provides the following technical solutions:
[0005] One of the technical solutions of the present invention is a B microalloying (CrCoNi) 94The Al3Ti3 medium entropy alloy comprises the following components, measured by weight percentage: 30.0%≤Cr≤31.2%, 36.5%≤Co≤37.3%, 29.0%≤Ni≤29.8%, 1.0%≤Al≤1.5%, 2.5%≤Ti≤3.0%, 0.02%≤B≤0.05%, and the balance being other inevitable impurity elements.
[0006] The second technical solution of the present invention is a kind of B microalloying (CrCoNi) 94 Preparation method of Al3Ti3 medium entropy alloy, according to the B microalloying (CrCoNi) 94 After the components in the Al3Ti3 medium entropy alloy are prepared, smelting, casting, homogenization treatment, solution treatment and aging treatment are carried out in sequence.
[0007] The third technical solution of the present invention is a method of inhibiting (CrCoNi) 94 Microalloying method for precipitation of Cr-rich sigma phase in Al3Ti3 medium entropy alloy, to (CrCoNi) 94 Adding B element to Al3Ti3 entropy alloy to obtain B microalloy (CrCoNi) 94 Al3Ti3 medium entropy alloy.
[0008] Preferably, by weight percentage, the B element is present in B microalloying (CrCoNi) 94 The proportion of entropy alloy in Al3Ti3 is 0.02-0.05%.
[0009] The present invention discloses the following technical effects:
[0010] The present invention adds B element (CrCoNi) 94 Compared with the B-free (CrCoNi) Al3Ti3 medium entropy alloy 94 In the Al3Ti3 medium entropy alloy, the size of the Cr-rich sigma phase is controlled, the number of fine and dispersed Cr-rich sigma phases is large, and the average grain size is smaller.
[0011] (CrCoNi) to which B is added in the present invention 94 In Al3Ti3 medium entropy alloy, the precipitation of Cr-rich sigma phase is suppressed, the size of the precipitated phase is significantly reduced, and the precipitation and growth of Cr-rich sigma phase are suppressed, making (CrCoNi) 94 The Al3Ti3 medium-entropy alloy avoids the severe precipitation of Cr-rich sigma phase during the process of strengthening the L12 phase precipitation, improves its corrosion resistance, and can be used in more complex environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0013] Figure 1 The microscopic morphology of the medium-entropy alloy of Comparative Example 1 under a high-resolution electron microscope, wherein (a) is a Cr-rich sigma phase, and (b) is an energy spectrum of the Cr element in the Cr-rich sigma phase.
[0014] Figure 2 The microscopic morphology pictures of the medium-entropy alloys of Example 1 and Comparative Example 1, wherein (a) is Comparative Example 1 and (b) is Example 1.
[0015] Figure 3 The microscopic morphology pictures of the medium-entropy alloys of Examples 1 and 2, wherein (a) is Example 2 and (b) is Example 1.
[0016] Figure 4 These are microscopic morphology pictures of the medium-entropy alloys of Examples 3 and 4, wherein (a) is Example 3 and (b) is Example 4.
[0017] Figure 5 The microscopic morphology of the medium-entropy alloys of Example 1, Example 2 and Comparative Example 1 after electrochemical testing, wherein (a) and (d) are Comparative Example 1 at 1000 times and 5000 times, respectively, (b) and (e) are Example 1 at 1000 times and 5000 times, respectively, and (c) and (f) are Example 2 at 1000 times and 5000 times, respectively.
[0018] Figure 6 The microscopic morphology images of the medium-entropy alloys of Comparative Example 2 and Comparative Example 3, wherein (a) is Comparative Example 2 and (b) is Comparative Example 3.
[0019] Figure 7 It is a graph showing the potential kinetic polarization test curves of the medium-entropy alloys of Example 1, Example 2 and Comparative Example 1. DETAILED DESCRIPTION
[0020] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0021] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0022] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0023] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0024] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0025] The present invention provides a B microalloy (CrCoNi) 94 The Al3Ti3 medium entropy alloy comprises the following components, measured by weight percentage: 30.0%≤Cr≤31.2%, 36.5%≤Co≤37.3%, 29.0%≤Ni≤29.8%, 1.0%≤Al≤1.5%, 2.5%≤Ti≤3.0%, 0.02%≤B≤0.05%, and the balance being other inevitable impurity elements.
[0026] In some embodiments of the present invention, the B microalloy (CrCoNi) is 94 The Al3Ti3 medium entropy alloy includes the following components: 30.0%≤Cr≤30.3%, 36.6%≤Co≤37%, 29.0%≤Ni≤29.2%, 1.4%≤Al≤1.5%, 2.5%≤Ti≤3.7%, 0.02%≤B≤0.04%, and the balance is other inevitable impurity elements.
[0027] In some embodiments of the present invention, the B microalloy (CrCoNi) is 94 The Al3Ti3 medium entropy alloy includes the following components: Cr 30.17%, Co 36.69%, Ni 29.08%, Al 1.46%, Ti 2.6%, B0.02%, and the balance is other inevitable impurity elements.
[0028] The present invention adopts (CrCoNi) 94 The addition of B element in Al3Ti3 entropy alloy limits the size of Cr-rich sigma phase, reduces the precipitation of Cr-rich sigma phase, and thus improves (CrCoNi) 94 The grain boundary brittleness of Al3Ti3 medium entropy alloy improves its corrosion resistance.
[0029] The present invention also provides the B microalloying (CrCoNi) 94 Preparation method of Al3Ti3 medium entropy alloy, according to the B microalloying (CrCoNi) 94 After the components in the Al3Ti3 medium entropy alloy are prepared, smelting, casting, homogenization treatment, solution treatment and aging treatment are carried out in sequence.
[0030] In some embodiments of the present invention, the homogenization treatment is carried out at a temperature of 1150-1250° C. and for a time of 1-3 h.
[0031] In some embodiments of the present invention, the homogenization treatment is performed at a temperature of 1200° C. for 2 hours.
[0032] In some embodiments of the present invention, the temperature of the solution treatment is 1100-1200° C., and the time is 5-15 min.
[0033] In some embodiments of the present invention, the temperature of the solution treatment is 1150° C. and the time is 10 min.
[0034] In some embodiments of the present invention, the aging treatment is performed at a temperature of 700-800° C. for 30 minutes.
[0035] In some embodiments of the present invention, the aging treatment is performed at a temperature of 700 or 800° C. and for 30 minutes.
[0036] In the present invention, if the aging temperature is increased (eg, 900°C), the Cr-rich sigma phase is almost completely dissolved back, the precipitation inhibition effect of B on the Cr-rich sigma phase is weakened, and the material itself cannot be used at 900°C.
[0037] The present invention also provides a method for inhibiting (CrCoNi) 94Microalloying method for precipitation of Cr-rich sigma phase in Al3Ti3 medium entropy alloy, to (CrCoNi) 94 Adding B element to Al3Ti3 entropy alloy to obtain B microalloy (CrCoNi) 94 Al3Ti3 medium entropy alloy.
[0038] In some embodiments of the present invention, the B element is present in the B microalloy (CrCoNi) by weight percentage. 94 The proportion of entropy alloy in Al3Ti3 is 0.02-0.05%, preferably 0.02% or 0.05%.
[0039] The B element can not only improve the strength and hot working properties of the alloy, but also segregate to the grain boundary and optimize the distribution of the secondary phase. 94 For Al3Ti3 medium entropy alloy materials, when the B element is distributed at the phase interface of the Cr-rich sigma phase, the size of the Cr-rich sigma phase can be controlled and the precipitation of the Cr-rich sigma phase can be inhibited.
[0040] In some embodiments of the present invention, the B microalloy (CrCoNi) is 94 The Al3Ti3 medium entropy alloy includes the following components: 30.0%≤Cr≤31.2%, 36.5%≤Co≤37.3%, 29.0%≤Ni≤29.8%, 1.0%≤Al≤1.5%, 2.5%≤Ti≤3.0%, 0.02%≤B≤0.05%, and the balance is other inevitable impurity elements.
[0041] In some embodiments of the present invention, the B microalloy (CrCoNi) is 94 The Al3Ti3 medium entropy alloy includes the following components: 30.0%≤Cr≤30.3%, 36.6%≤Co≤37%, 29.0%≤Ni≤29.2%, 1.4%≤Al≤1.5%, 2.5%≤Ti≤3.7%, 0.02%≤B≤0.04%, and the balance is other inevitable impurity elements.
[0042] In some embodiments of the present invention, the B microalloy (CrCoNi) is 94 The Al3Ti3 medium entropy alloy includes the following components: Cr 30.17%, Co 36.69%, Ni 29.08%, Al 1.46%, Ti 2.6%, B0.02%, and the balance is other inevitable impurity elements.
[0043] In some embodiments of the present invention, according to the B microalloying (CrCoNi) 94After the components of the Al3Ti3 mesentrotropic alloy are prepared, smelting, casting, homogenization, solution treatment and aging treatment are carried out in sequence.
[0044] In some embodiments of the present invention, the homogenization treatment is carried out at a temperature of 1150-1250° C. and for a time of 1-3 h.
[0045] In some embodiments of the present invention, the homogenization treatment is performed at a temperature of 1200° C. for 2 hours.
[0046] In some embodiments of the present invention, the temperature of the solution treatment is 1100-1200° C. and the time is 10-15 min.
[0047] In some embodiments of the present invention, the temperature of the solution treatment is 1150° C. and the time is 10 min.
[0048] In some embodiments of the present invention, after the solution treatment, a step of water cooling to room temperature is also included.
[0049] In some embodiments of the present invention, the aging treatment is performed at a temperature of 700-800° C. for 30 minutes.
[0050] In some embodiments of the present invention, the aging treatment is performed at a temperature of 700 or 800° C. and for 30 minutes.
[0051] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0052] Example 1
[0053] This embodiment provides a B microalloy (CrCoNi) 94 Al3Ti3 medium entropy alloy (referred to as medium entropy alloy), by weight percentage, has the following components: Cr 30.17%, Co 36.69%, Ni 29.08%, Al 1.46%, Ti 2.6%, B 0.02%, and the remainder is other unavoidable impurity elements. The preparation steps are as follows:
[0054] The raw materials according to the composition ratio of the above-mentioned medium-entropy alloy are smelted in a vacuum induction furnace, cast into an ingot of 120×100×500mm under vacuum, air-cooled, and demolded when cooled to room temperature; then the ingot is placed in a resistance heating furnace at 1200℃ for homogenization treatment for 2h, air-cooled to room temperature, cold-rolled to 0.8mm, and the sample is continued to be placed in a resistance heating furnace and heated to 1150℃ for solution treatment for 10min. After water cooling to room temperature, it is aged at 700℃ for 30min.
[0055] Comparative Example 1
[0056] This comparative example provides a (CrCoNi) 94 The Al3Ti3 medium entropy alloy (referred to as medium entropy alloy) has the following components by weight percentage: Cr 30.17%, Co 36.69%, Ni 29.08%, Al 1.46%, Ti 2.6%, and the remainder is other inevitable impurity elements. The preparation method is the same as that of Example 1.
[0057] 10 mm×10 mm×0.8 mm samples were cut from the medium entropy alloy sheets prepared in Example 1 and Comparative Example 1, the prepared samples were ground with sandpaper of different meshes and then electropolished, and the microscopic morphology of the samples was analyzed using a scanning electron microscope.
[0058] Figure 1 The microscopic morphology of the sample of the medium-entropy alloy of Comparative Example 1 under high-resolution electron microscope, wherein (a) is a Cr-rich sigma phase, and (b) is an energy spectrum of the Cr element in the Cr-rich sigma phase.
[0059] Figure 2 The microscopic morphology of the medium entropy alloy of Example 1 and Comparative Example 1 shows that the size of the Cr-rich precipitate phase at the grain boundary of the 0.02% B sample (Example 1) is smaller than that of the 0% B (Comparative Example 1) sample, and the surrounding L12 phase exists in a larger area. This shows that the addition of element B (CrCoNi) 94 The precipitation of Cr-rich sigma phase in the Al3Ti3 medium entropy alloy is suppressed compared with the sample without addition (Comparative Example 1). Therefore, it can be seen that the B element has a strong inhibitory effect on the precipitation of Cr-rich sigma phase.
[0060] Example 2
[0061] This embodiment provides a B microalloy (CrCoNi) 94 The Al3Ti3 medium entropy alloy (referred to as medium entropy alloy) has the following components by weight percentage: Cr 30.16%, Co 36.67%, Ni 29.06%, Al 1.46%, Ti 2.59%, B0.05%, and the remainder is other inevitable impurity elements. The preparation method is the same as that of Example 1.
[0062] 10mm×10mm×0.8mm samples were cut from the medium entropy alloy sheets prepared in Example 1 and Example 2, and the prepared samples were electrolytically polished after grinding with sandpaper of different meshes. The microscopic morphology of the samples was analyzed using a scanning electron microscope. Figure 3As shown in (a) and (b), the 0.02% B sample (Example 1) is compared with the 0.05% B sample (Example 2). The 0.05% B (Example 2) sample B has a weakened inhibitory effect on the Cr-rich precipitation phase at the grain boundary, which is manifested in the increase in the volume of the Cr-rich sigma phase and the increase in the area where the L12 phase exists; the L12 phase area around the larger Cr-rich sigma phase is significantly increased. Therefore, it can be seen that when the B element is 0.05wt%, the inhibition of the precipitation of the sigma phase by the B element is weakened compared with the case when the B element is 0.02wt%, but compared with no addition of the B element, it still has an inhibitory effect on the Cr-rich sigma phase.
[0063] 12mm×12mm×1mm samples were cut from the medium entropy alloy sheets prepared in Example 1, Comparative Example 1 and Example 2, and the prepared samples were mechanically polished after grinding with different sandpapers. The samples were subjected to electrochemical polarization tests in 0.2mol / L H2SO4 solution. The micromorphology of the samples after the electrochemical test was analyzed by scanning electron microscopy (such as Figure 5 (a), (b), (c)), the corrosion potential and corrosion current density are shown in Table 1 and Figure 7 As shown ( Figure 7 In the figure, B0 represents comparative example 1, B0.02 represents example 1, and B0.05 represents example 2).
[0064] Table 1 Corrosion potential and corrosion current density
[0065]
[0066] Combination Figure 5 As can be seen from Table 1, adding B element can improve (CrCoNi) 94 The corrosion resistance of Al3Ti3 medium entropy alloy is significantly improved when the addition amount of B element is 0.02%. 94 The corrosion resistance of Al3Ti3 medium entropy alloy is most significantly improved.
[0067] Example 3
[0068] The B microalloying (CrCoNi) provided in this embodiment 94 The composition and preparation method of the Al3Ti3 medium entropy alloy (referred to as medium entropy alloy) are the same as those in Example 1, the only difference being that the aging temperature is 800°C.
[0069] Example 4
[0070] The B microalloying (CrCoNi) provided in this embodiment 94 The composition and preparation method of the Al3Ti3 medium entropy alloy (referred to as medium entropy alloy) are the same as those of Example 2, the only difference being that the aging temperature is 800°C.
[0071] Comparative Example 2
[0072] The B microalloy (CrCoNi) provided in this comparative example 94 The composition and preparation method of the Al3Ti3 medium entropy alloy (referred to as medium entropy alloy) are the same as those in Example 1, the only difference being that the aging temperature is 900°C.
[0073] Comparative Example 3
[0074] The B microalloy (CrCoNi) provided in this comparative example 94 The composition and preparation method of the Al3Ti3 medium entropy alloy (referred to as medium entropy alloy) are the same as those of Example 2, the only difference being that the aging temperature is 900°C.
[0075] Figure 6 The microscopic morphology of the medium-entropy alloys of Comparative Examples 2 and 3 shows that when the aging treatment temperature is selected to be 900°C, the Cr-rich sigma phase is almost completely dissolved back, the inhibitory effect of B on the precipitation of the Cr-rich sigma phase is weakened, and the material itself cannot be used at 900°C.
[0076] In summary, after adding B element (CrCoNi) 94 The precipitation and growth of the entropy alloy sigma phase in Al3Ti3 is suppressed. When the addition amount of B element is 0.02%, the Cr-rich sigma phase is finer, less in number and more dispersed, and the grain size is also smaller, which has the most significant improvement on the corrosion resistance of the material. The experimental results show that the inhibitory effect of B element on the growth of Cr-rich sigma phase at the phase interface can be fully utilized by microalloying, limiting the precipitation of Cr-rich sigma phase and improving the corrosion resistance of the material.
[0077] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A B microalloy (CrCoNi) 94 Al3Ti3 medium entropy alloy, characterized in that Measured by weight percentage, the steel comprises the following components: 30.0%≤Cr≤31.2%, 36.5%≤Co≤37.3%, 29.0%≤Ni≤29.8%, 1.0%≤Al≤1.5%, 2.5%≤Ti≤3.0%, 0.02%≤B≤0.05%, and the remainder is other inevitable impurity elements.
2. A B microalloy (CrCoNi) as claimed in claim 1 94 The preparation method of Al3Ti3 medium entropy alloy is characterized in that: B microalloyed as described (CrCoNi) 94 After the components in the Al3Ti3 medium entropy alloy are prepared, smelting, casting, homogenization treatment, solution treatment and aging treatment are carried out in sequence.
3. B microalloying (CrCoNi) according to claim 2 94 The preparation method of Al3Ti3 medium entropy alloy is characterized in that: The homogenization temperature is 1150-1250°C and the time is 1-3h; The temperature of the solution treatment is 1100-1200°C and the time is 5-15min; The aging treatment is carried out at a temperature of 700-800°C and for 30 minutes.
4. An inhibition (CrCoNi) 94 A microalloying method for precipitation of Cr-rich sigma phase in Al3Ti3 medium entropy alloy, characterized in that: To (CrCoNi) 94 Adding B element to Al3Ti3 entropy alloy to obtain B microalloy (CrCoNi) 94 Al3Ti3 medium entropy alloy.
5. The inhibition according to claim 4 (CrCoNi) 94 A microalloying method for precipitation of Cr-rich sigma phase in Al3Ti3 medium entropy alloy, characterized in that: In terms of weight percentage, the B element in B microalloying (CrCoNi) 94 The proportion of entropy alloy in Al3Ti3 is 0.02-0.05%.
6. The inhibition according to claim 4 (CrCoNi) 94 A microalloying method for precipitation of Cr-rich sigma phase in Al3Ti3 medium entropy alloy, characterized in that: In terms of weight percentage, the B microalloy (CrCoNi) 94 The Al3Ti3 medium entropy alloy includes the following components: 30.0%≤Cr≤31.2%, 36.5%≤Co≤37.3%, 29.0%≤Ni≤29.8%, 1.0%≤Al≤1.5%, 2.5%≤Ti≤3.0%, 0.02%≤B≤0.05%, and the balance is other inevitable impurity elements.
7. The inhibition according to claim 6 (CrCoNi) 94 A microalloying method for precipitation of Cr-rich sigma phase in Al3Ti3 medium entropy alloy, characterized in that: According to the B microalloying (CrCoNi) 94 After the components of the Al3Ti3 mesentrotropic alloy are prepared, smelting, casting, homogenization, solution treatment and aging treatment are carried out in sequence.
8. The inhibition according to claim 7 (CrCoNi) 94 A microalloying method for precipitation of Cr-rich sigma phase in Al3Ti3 medium entropy alloy, characterized in that: The temperature of the homogenization treatment is 1150-1250° C. and the time is 1-3 hours.
9. The inhibition according to claim 7 (CrCoNi) 94 A microalloying method for precipitation of Cr-rich sigma phase in Al3Ti3 medium entropy alloy, characterized in that: The temperature of the solution treatment is 1100-1200° C. and the time is 5-15 minutes.
10. The inhibition according to claim 7 (CrCoNi) 94 A microalloying method for precipitation of Cr-rich sigma phase in Al3Ti3 medium entropy alloy, characterized in that: The aging treatment is carried out at a temperature of 700-800°C and for 30 minutes.
Citation Information
Patent Citations
Ni-Cr-Co-Mo-Al-Ti high-temperature alloy material and preparation method thereof
CN106702217A
High-toughness medium entropy high temperature alloy and preparing method thereof
CN111500917A
2.0 GPa-grade ultrahigh-yield-strength plastic CoCrNi-based medium-entropy alloy and preparation method thereof
CN114086049A
High-toughness heterogeneous multiphase core-shell structure medium-entropy alloy and preparation method thereof
CN115198162A
CoCrNi-based medium-entropy alloy strengthened by nano coherent precipitation with high aluminum content and high titanium content and preparation method of CoCrNi-based medium-entropy alloy
CN115233077A
